Compostagem da borra de óleos e gorduras residuais com bagaço de cana-de-açúcar e esterco bovino - OLIVEIRA, Elieser Parcero (2013)
It was studied the behavior of the main parameters of an aerobic composting process by incorporating the sludge settling and filtering of Waste Oils and Fats (WOF) for the production of biodiesel. Aiming proper disposal of sludge generated by the pre - treatment of WOF, composting experiment was conducted in a completely randomized design with five treatments and three replications being incorporated into the sludge at different doses, to an organic substrate containing bagasse sugarcane crushed cattle manure in the proportions of 30 and 70 % respectively. The mixture was distributed in plastic containers of 50 liters, under an area protected from the weather and the composting process had direct monitoring phase mesophilic, thermophilic and final stabilization until the formation of humified material. The process was monitored by the parameters temperature, pH, volatile solids, electrical conductivity, moisture, aeration and C / N ratio. At the end of the composting experiment was conducted to test biological growth Lycopersicum esculentum Mill, by administering increasing doses of the compounds obtained by checking the germination, development and total weight of the plants at 24 days of vegetative growth. The data were organized, tabulated and applied an Analysis of Variance Simple (ANOVA), adopting a statistical probability of 0.05. The results showed interference during composting and sludge on seed germination and plant growth when doses were in excess of 20%. The compounds obtained were within the minimum standards set by the Ministry of Agriculture, Livestock and Supply.